Fundamentals of Ge1−xSnx and SiyGe1−x-ySnx RPCVD epitaxy. (1st November 2017) - Margetis, Joe; Mosleh, Aboozar; Ghetmiri, Seyed Amir; Al-Kabi, Sattar; Dou, Wei; Du, Wei; Bhargava, Nupur; Yu, Shui-Qing; Profijt, Harald; Kohen, David; Loo, Roger; Vohra, Anurag; et al.
Abstract: We have studied epitaxial growth of Ge1−x Snx and Siy Ge1−x-y Snx materials in 200 mm and 300 mm industrial CVD reactors using industry standard precursors. The growth kinetics of undoped GeSn were firstly studied via varying growth parameters including growth temperatures, GeH4 and SnCl4 precursor flows, which indicated that the material growth is highly dependent on surface kinetic limitations involving the SnCl4 reaction pathway. Secondly, the growth kinetics of doped layer growth by varying the growth temperatures and the PH3 and B2 H6 dopants flows were investigated. It was shown that B2 H6 had the effect of increasing the growth rate and decreasing the Sn incorporation whereas PH3 had no effect on the growth rate but increased the Sn incorporation. Thirdly, the SiGeSn growth kinetics using SiH4, GeH4, and SnCl4 as precursors were discussed, which revealed that the careful control of the growth rate was required to produce compositionally homogenous SiGeSn alloy. Moreover, the material and optical characterizations have been conducted to examine the material quality. Finally, the GeSn quantum well structure was grown to exhibit the precise control of the growth parameters.